Analisis Usability Sistem Informasi Pengajuan Layanan Administrasi Dan Tugas Akhir Jurusan Teknologi Informasi Metode Heuristic Evaluation : Usability Analysis of Information System for Submission of Administrative Services and Final Assignment of Information Technology Department Heuristic Evaluation Method - Mutia; Syahrullah; Kasim, Anita Ahmad; Pusadan, Mohammad Yazdi (Technomedia Journal, 2024)
ABSTRACT The administrative and final project service submission system is an information system that will be used at the Information Technology Department of Tadulako University in terms of carrying out the administrative process and final assignments for both lecturers, education staff, and students. SIPENDEKAR is designed for lecturers, education personnel, and students SIPENDEKAR is designed to integrate all administrative processes and final assignments. This research uses the heuristic evaluation method . The heuristic evaluation method is a method used to identify problems in the use of interface design, so that usability problems can be corrected through the redesign process. Through the application of Heuristic Evaluation, we can find obstacles and receive suggestions for improvement from experts based on usability principles that apply to websites that have 10 principles, namely Visibility of system status, Match between system and the real world, User control and freedom, Consistency and standards, Error Prevention, Recongnition rather than recall, Flexibility and efficiency of use, Aesthetic and minimalist design, Help users recognize, Dialogue, and recovers from errors, and Help and documentation. The questionnaire testing involved 37 respondents, the results of the validity and reliability test were declared valid and reliable.This research uses 6 research stages Identification of problems and literature studies, determination of evaluation methods, preparation for evaluation, and preparation for evaluation.